Screening of Rice Cultivars Suitable for Early Transplanting in Haor Agriculture - Sarwar, A.K.M. Golam; Chanda, Sontosh Chandra; Islam , Md. Mozahidul; Jannat-E-Tajkia (Journal of the Bangladesh Agricultural University, 2024)
An experiment was conducted at the farmer’s field in Dowarabazar, Sunamganj during November 2018 to April 2019 to find out suitable cultivar(s) for early transplanting mediated low-temperature stress tolerance in boro season to avoid the flash flooding. Twelve hybrid rice cultivars, viz. BRRI hybrid dhan2, BRRI hybrid dhan3, BRRI hybrid dhan5, SL-8H, Hybrid LP-70, Agomoni JBS-17(4), Win-302, Winall Hybrid 2, Nobin IS-1, Ispahani 1, Durbar IS-2 and Ispahani 2, were used as experimental materials. The field experiment was laid out in a randomized complete block design with three replications. The standard rice cultivation procedure was followed. Growth and yield contributing descriptors e.g., plant height, number of effective tillers, panicle length, grain yield, etc. differed significantly among the cultivars. Among the studied cultivars, BRRI hybrid dhan5 produced maximum grain yield (5.90 t ha–1) followed by cultivar Nobin IS-1 (5.88 t ha–1). The lowest yield was recorded from Ishpahani 2 (3.44 t ha–1) and the other cultivars produced intermediate yield. It would be concluded that among the studied cultivars, BRRI hybrid dhan5 and Nobin IS-1 could be recommended for early transplanting within the haor area. J Bangladesh Agril Univ 18(4): 963–967, 2020 https://doi.org/10.5455/JBAU.25243